Indonesia's Party Court: Jurisdictional Ambiguity, Overlapping Authority, and the Structuring of Rule of Law of Political Parties Law (No. 2/2011) - Achmad Sodik Sudrajat (Faculty of Law, Universitas Pasundan, 2025)
The creation of the Political Party Court was a first step towards party accountability and cohesion, as per Law No. 2 of 2011 in relation to Political Parties (Republic of Indonesia). Despite its crucial function, the position of the law in Indonesia is still unclear, and it frequently competes with official courts like the Constitutional Court. The interpretation of Article 33 (1) and (2) has shown that it can potentially create legal instability and interfere with the resolution of disputes, undermine the legitimacy of democratic elections, or subvert decisions made by the constitutional court. Additionally, the Party Court's ambiguity in its jurisdiction undermines the legal credibility of final Constitutional Court decisions, despite extensive research being undertaken on its role in election conflicts. Additionally, there is a significant research gap in assessing the specific legal and institutional procedures. In order to understand how the Constitutional Court's decisions can impact Indonesian general elections, this paper examines the legal uncertainties that arise from party disputes. By using a qualitative juridical-normative technique, the study investigates statutes, court opinions, and doctrine in relation to election law. It concludes by indicating that